Immobilization of lipases via interfacial activation on hydrophobic supports: Production of biocatalysts libraries by altering the immobilization conditions - Arana-Peña, Sara; Rios, Nathalia S.; Carballares, Diego; Gonçalves, Luciana R. B.; Fernández-Lafuente, Roberto (Catalysis Today, 2020)
Lipases A and B from Candida antarctica (CALA, CALB), and those from Candida rugosa (CRL) and Rhizomucor miehei (RML) have been immobilized on octyl agarose beads under 16 different conditions. The activities of the biocatalysts versus different substrates were analyzed, as well as their thermal stabilities at pH 7.0. All CALB and CRL preparations showed very similar properties, except the CRL biocatalysts prepared at pH 9. Under these conditions the free enzyme was partially inactivated. Immobilized CALA showed some significant differences in activity depending on the immobilization conditions when using esters of mandelic acid as substrates (the activities of the different preparations differed by more than a 2-fold factor), while when using the other substrates the differences were minimal. However, immobilized RML enzyme greatly alters its activity depending on the immobilization conditions, reaching differences up to 4–5 fold in both activity and stability. It is remarkable that the effect of one immobilization variable depends on the substrates, and that there are strong interactions between the different immobilization variables. Thus, this immobilization method was very robust (producing almost identical functional biocatalysts independently from the immobilization conditions) using CRL or CALB, while the immobilization conditions must be carefully controlled using RML to have reproducible results. © 2020 Elsevier B.V. We gratefully recognize the support from the MICINN from Spanish Government, (project number CTQ2017-86170-R). NSR thanks to CNPq for a predoctoral fellowship (CNPq scholarship– Brazil) and to Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (PNPD/ CAPES) for a postdoctoral fellowship. DC gratefully thanks for a pre doctotal FPI fellowship to MICINN, Spain. Mr Martinez (Novozymes Spain) is gratefully recognized by the donation of the enzymes. Peer reviewed